Revisión sistemática sobre los métodos de extracción y purificación en el bioprocesamiento de pectinasas aplicadas en la clarificación de zumos frutales - Coque Tutasig, Lisset Evelin (2023)
The main objective of this work is to identify the methods of extraction and purification in the bioprocessing of pectinases applied in the clarification of fruit juices. In this research, a bibliographical review was carried out starting with the identification of the documentary sources and collecting information to later select it with the help of a fourphase flowchart, established within the PRISMA method, resulting in 15 articles that were analyzed in their totality. A comparative matrix of the methods used to obtain and purify enzymes was elaborated, in addition, the process that must be carried out to obtain them on a small scale was detailed, this in order to determine the most efficient methods that allow having a purified enzyme. that can later be applied in fruit juice clarification processes in a laboratory. From this investigation it was possible to verify that 80% of the authors agree that the precipitation methods by ammonium sulfate and ionic chromatography helped to have a total purification, this accompanied by an extraction by centrifugation, resulting in a totally pure enzyme, which when applied in the clarification of fruit juices, it was the one that obtained the best results.